2015
DOI: 10.1093/mnras/stv1483
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and linear spectropolarimetry of the early Herbig Be stars PDS 27 and PDS 37

Abstract: The number of well-studied early-type pre-main-sequence objects is very limited, hampering the study of massive star formation from an observational point of view. Here, we present the results of VLT/FORS2 spectropolarimetric and VLT/X-shooter spectroscopic observations of two recently recognised candidate Herbig Be stars, PDS 27 and PDS 37. Through analysis of spectral lines and photometry, we find that these two objects are hot, 17500 ± 3500 K, have large radii, 17.0 ± 4.0 and 25.8 ± 5.0 R ⊙ , and are very m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 53 publications
1
16
1
Order By: Relevance
“…This argument is supported by the observed line effects across the absorptive component of Hα in PDS 27, PDS 37 and PDS 133, as the line effect is stronger for a weaker absorption component. Ababakr et al (2015) suggested a similar scenario in an in-depth study of PDS 27 and PDS 37, but here we have an extra object that follows the same pattern.…”
Section: Mclean Effectsupporting
confidence: 74%
See 4 more Smart Citations
“…This argument is supported by the observed line effects across the absorptive component of Hα in PDS 27, PDS 37 and PDS 133, as the line effect is stronger for a weaker absorption component. Ababakr et al (2015) suggested a similar scenario in an in-depth study of PDS 27 and PDS 37, but here we have an extra object that follows the same pattern.…”
Section: Mclean Effectsupporting
confidence: 74%
“…A1) in appendix A). PDS 37 shows a possible line effect in only the first two datasets while the second two datasets do not show such a line effect (Ababakr et al 2015). Therefore, the line effect in PDS 37 is not a conclusive result based on the current data.…”
Section: Ca II Linesmentioning
confidence: 71%
See 3 more Smart Citations